Chemical characterization and evaluation of gastric antiulcer properties of the hydroethanolic extract of the stem bark of Virola elongata (Benth.) Warb. (1st March 2019) - Almeida, Guilherme Vieira Botelho de; Arunachalam, Karuppusamy; Balogun, Sikiru Olaitan; Pavan, Eduarda; Ascêncio, Sérgio Donizeti; Soares, Ilsamar Mendes; Zanatta, Ana C.; Vilegas, Wagner; Macho, Antonio; Oliveira Martins, Domingos Tabajara de
Abstract: Ethnopharmacological relevance: Virola elongata is a tree species belonging to the Myristicaceae family, distributed in the North and Midwest regions of Brazil, in the phytogeographic domain of the Amazon. The aqueous infusion or the hydroethanolic macerate of the stem bark of V. elongata are used in Brazilian and Ecuadorian indigenous folk medicine for several ethnopharmacological purposes, principally, in the treatment of stomach pain, indigestions, and gastric ulcers. This study was aimed to investigate the gastroprotective activity of this plant in order to support its popular use with scientific evidence. Materials and methods: The stem bark hydroethanolic extract of the plant (HEVe) was prepared by maceration. Its qualitative and quantitative phytochemical constituents were investigated by classical colorimetric techniques, HPLC, and electrospray ionization-multiple stage fragmentation (ESI-MS n ). The gastroprotective and antiulcer activity of HEVe at doses of 100, 300 and 900 mg/kg p.o. were tested using three acute (acidified ethanol, piroxicam, and in-water-restrain stress), and one chronic (acetic acid) animal ulcer models. The probable mode of action of the HEVe was evaluated by analyzing gastric acid secretion, mucus content, nitric oxide effect, and its antioxidant properties (on catalase, myeloperoxidase, and GSH content) in experimental rodents. The direct extract's activity on the growth of Helicobacter pylori was also investigated. Results: Total phenolic content in the HEVe was of 146.20 ± 1.07 mg, being flavonoids about 50% (71.79 ± 0.70 mg) of it. Comparative HPLC fingerprint analysis revealed the presence of known phenolic antiulcer compounds, such as gallic acid, catechin, and rutin. Also, methanol/water fractionation and ESI-MS n analysis of the HEVe reveals the presence of quinic acid, 3, 3′, 4-trihydroxystilbene, juruenolid D, one catechin dimer, one C-glycosyl flavonoid, one polyketide and two neolignans as the major components of the extract. The HEVe attenuated gastric ulceration in all the different models of acute gastric ulcer, by enhancing gastroprotection through its antioxidant properties in vivo, and reducing also considerably the gastric secretion and total acidity. The HEVe also presented healing properties against the induced chronic ulceration process. On the other hand, the HEVe did not exhibit direct activity against H. pylori . Conclusion: The HEVe exhibited significant gastroprotective/antiulcer effects and contain a relative high proportion of phenolic compounds, especially flavonoids, that could likely account, at least in part, for its pharmacological properties. The results justify its traditional usage and provided scientific evidence for its potential as a new herbal medicine to treat gastric ulcers. Graphical abstract: